Performance Evaluation of In-Plan Irregular RC Frame Buildings Based on Turkish Seismic Code - Arslan, Guray; Borekci, Muzaffer; Sahin, Baris; Denizer, M. Ilker; Duman, Kutay S. (SPRINGER INTERNATIONAL PUBLISHING AG, 2018)
Torsional irregularity, such as beam discontinuity and asymmetry in plan, can be seen widely in common buildings and it has a considerable effect on seismic performance of a building. In this study, 8 different five- and seven-storey RC frame buildings with and without beam discontinuity in plan and with different torsional irregularities were designed according to Turkish Seismic Code 2007 and performance evaluations of these buildings were carried out using different performance evaluation methods: (1) linear elastic method (LEM), (2) nonlinear static procedure (NSP), and (3) nonlinear time history analysis (NTA). Life safety performance level was chosen as target performance level. It is observed that NSP delivers closer results to the results of NTA than LEM does when the considered building has in-plan irregularity. Using LEM in performance evaluation of an in-plan irregular building can yield unreliable and conservative results. It is concluded that if torsional irregularity without beam discontinuity is smaller than the code limits, it may not have a considerable effect on seismic performance of buildings.
Keywords: Seismic performance evaluation; Torsional irregularity; Asymmetric buildings; RC structures; PUSHOVER ANALYSIS PROCEDURE; DEMANDS; RISE; Engineering